Analisis Techno-Economic Integrasi PLTS Atap pada UMKM Industri Pangan Menggunakan Simulasi PVsyst untuk Reduksi Biaya Energi Listrik - Bagus Pramono; Nugroho Tri Waskitho (Journal of Educational Engineering and Environment, 2026)
The increasing electricity demand in Indonesia’s small and medium enterprise (SME) sector has encouraged the adoption of renewable energy technologies to improve energy efficiency and reduce operational costs. This study aims to evaluate the technical and economic feasibility of integrating a grid-connected rooftop photovoltaic (PV) system at Diva Bakery, a food-processing SME located in Banyuwangi, East Java, Indonesia. The system was designed using a rooftop maximum capacity scenario and simulated using PVsyst software, while economic feasibility was assessed through discounted cash flow analysis. The proposed system has an installed capacity of 4.95 kWp, consisting of 9 monocrystalline PV modules rated at 550 Wp and a 4 kW grid-tied inverter. Simulation results indicate that the system can generate 8,288.4 kWh/year, with a specific yield of 1,674 kWh/kWp/year and a performance ratio of 80.51%, demonstrating good technical performance under tropical climatic conditions. The largest system loss was attributed to temperature effects, highlighting the importance of proper ventilation and installation design. Economic analysis shows an annual electricity cost saving of IDR 14.09 million, with a Net Present Value (NPV) of IDR 58.4 million, an Internal Rate of Return (IRR) of 18.7%, a discounted payback period of 5.4 years, and a Levelized Cost of Energy (LCOE) of IDR 986/kWh, which is lower than the applicable PLN electricity tariff. In addition, the system is estimated to reduce carbon emissions by approximately 6.08 tons CO₂/year. The results confirm that rooftop PV implementation in food-processing SMEs is technically feasible, economically attractive, and environmentally beneficial, making it a promising strategy to enhance SME competitiveness and support Indonesia’s clean energy transition. Keywords: Rooftop photovoltaic, techno-economic analysis, SMEs, PVsyst, renewable energy.